2020
DOI: 10.1103/physrevresearch.2.013062
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous chiral edge states in spin-1 Dirac quantum dots

Abstract: We uncover an unexpected family of in-gap chiral edge states in noninverted spin-1 Dirac quantum dots. The system represents a topologically trivial confinement configuration where such edge states are not expected according to the conventional wisdom. In particular, for a massive type of confining potential, two distinct situations can arise: with or without mass sign change, corresponding to a quantum dot with or without band inversion, respectively. The former case is conventional, where topologically prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…For example, the orbital susceptibility 17,18 and the topological berry phase 19 can be tuned with the parameter α, and in contrast with graphene the plasmon branch is pinched in to a single point 20 . More recently, it has been found that this kind of Hamiltonian leads to an unexpected family of in-gap chiral edge states for noninverted spin-1 Dirac quantum dots 21 . There are some other previous works concerning the structure of the electromagnetic-dressed electron spectrum [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the orbital susceptibility 17,18 and the topological berry phase 19 can be tuned with the parameter α, and in contrast with graphene the plasmon branch is pinched in to a single point 20 . More recently, it has been found that this kind of Hamiltonian leads to an unexpected family of in-gap chiral edge states for noninverted spin-1 Dirac quantum dots 21 . There are some other previous works concerning the structure of the electromagnetic-dressed electron spectrum [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…In comparing with the graphene, there is an extra lattice site (per unit cell) in the center of hexagon of honeycomb lattice 24 26 . The low-energy physics of the dice lattice are also described by the Dirac equation, but its pseudospin instead of 27 , 28 . There are two schemes to obtain this kind of lattices: one is to fabricate the trilayer structure of cubic lattice (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The above Eq. (28) shows that the integral of spectral functions is proportional to filling factor n − 3 (relative to the half filling). If the filling factor is half filling (n − 3 = 0), the integral of spectral functions is exactly zero.…”
Section: Two-particle Spectral Functionsmentioning
confidence: 99%